2001
DOI: 10.1016/s0092-8674(01)00438-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Kinetochore-Microtubule Attachment in Budding Yeast

Abstract: The complex series of movements that mediates chromosome segregation during mitosis is dependent on the attachment of microtubules to kinetochores, DNA-protein complexes that assemble on centromeric DNA. We describe the use of live-cell imaging and chromatin immunoprecipitation in S. cerevisiae to identify ten kinetochore subunits, among which are yeast homologs of microtubule binding proteins in animal cells. By analyzing conditional mutations in several of these proteins, we show that they are required for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
289
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(310 citation statements)
references
References 54 publications
20
289
1
Order By: Relevance
“…However, by performing immunofluorescence on chromosome spreads of insoluble nuclear material, we were able to detect the kinetochore localization of Ipl1p at metaphase, suggesting that Ipl1p is in the Aurora B family. Our localization results are similar to those recently published (He et al 2001). Finding Ipl1p at kinetochores is consistent with its role in the spindle checkpoint.…”
Section: Ipl1p Localizes To Kinetochores During Metaphasesupporting
confidence: 92%
“…However, by performing immunofluorescence on chromosome spreads of insoluble nuclear material, we were able to detect the kinetochore localization of Ipl1p at metaphase, suggesting that Ipl1p is in the Aurora B family. Our localization results are similar to those recently published (He et al 2001). Finding Ipl1p at kinetochores is consistent with its role in the spindle checkpoint.…”
Section: Ipl1p Localizes To Kinetochores During Metaphasesupporting
confidence: 92%
“…However, in contrast to studies that suggested the existence of CenH3-independent assembly pathways based on immunofluorescence data (Oegema et al, 2001;Goshima et al, 2003;Hayashi et al, 2004;Regnier et al, 2005), we found that all proteins tested exhibited some dependence on Cse4 when the ChIP technique was used to quantify occupancy. Although the inner kinetochore complex CBF3 was previously proposed to nucleate yeast kinetochore assembly (Russell et al, 1999;Goshima and Yanagida, 2000;He et al, 2001;Janke et al, 2001Janke et al, , 2002, our work shows that the centromeric nucleosome also has an essential role in kinetochore assembly. We therefore favor a model where the centromeric nucleosome creates a chromatin structure that cooperates with the binding of the inner CBF3 complex to initiate yeast kinetochore assembly.…”
Section: The Functions Of Cenh3mentioning
confidence: 54%
“…The inner kinetochore contains the CBF3 complex (Ndc10, Cep3, Skp1, and Ctf13) as well as the DNA binding proteins Mif2, Cbf1, and the yeast centromeric histone H3 variant (CenH3) Cse4. CBF3 binds directly to the centromeric DNA and is thought to nucleate kinetochore assembly because all kinetochore proteins require it for localization (Russell et al, 1999;Goshima and Yanagida, 2000;He et al, 2001;Janke et al, 2001Janke et al, , 2002. The central kinetochore contains the MTW1 (Mtw1, Dsn1, Nnf1, and Nsl1) and CTF19/COMA (Ctf19, Mcm16, Mcm19, Mcm21, Mcm22, Ctf3, Chl4, Okp1, Ame1, Iml3, Nkp1, and Nkp2) complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent data has suggested that knock down of one of these three proteins can cause concomittant reduction in the expression of other complex members. 10,14 The emerging view is that within the chromosomal passenger complex, aurora B kinase is the active component responsible for regulating biorientation of chromosomes during prometaphase, [15][16][17] while INCENP, survivin and borealin are thought to direct aurora B to its substrates and possibly enhance its kinase activity. 9,10,14,[18][19][20][21] Aurora B kinase has an ever growing list of substrates, which includes itself, 22 its fellow passengers, borealin, 12 INCENP, 18 and survivin 23 and a variety of other chromosomal associated proteins such as histone 3, 24 the kinI kinesin, MCAK [25][26][27] and topoisomerase II; 28 for reviews see refs.…”
Section: Introductionmentioning
confidence: 99%